2014
DOI: 10.1002/jssc.201400536
|View full text |Cite
|
Sign up to set email alerts
|

Multiresidue method for the determination of 227 pesticides in hot pepper (Capsicum annuum L.) by liquid chromatography with tandem mass spectrometry†

Abstract: A high-throughput, rapid, and efficient modified QuEChERS (quick, easy, cheap, effective, rugged, and safe) method with a simple cleanup procedure has been developed for simultaneously determining 227 pesticides in pepper samples by liquid chromatography with tandem mass spectrometry (running time: 10 min). Pesticide residues were extracted/partitioned with an acetonitrile/DisQuE QuEChERS pouch, and the resulting samples were cleaned up with different methods: dispersive solid-phase extraction with primary sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Few studies have recently reported analytical methods for measuring metrafenone. Metrafenone residue analysis is mainly performed via liquid chromatography with tandem mass spectrometry (LC-MS) (Yoann, David, Alain, & Pierre, 2010;Zhu, Zhao, Feng, & Kim, 2014). The above methods were all multi-residue analytical method of 227 and 242 kinds of pesticides, the probably range of recovery was from 70% to 120% in hot pepper, not detailed.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have recently reported analytical methods for measuring metrafenone. Metrafenone residue analysis is mainly performed via liquid chromatography with tandem mass spectrometry (LC-MS) (Yoann, David, Alain, & Pierre, 2010;Zhu, Zhao, Feng, & Kim, 2014). The above methods were all multi-residue analytical method of 227 and 242 kinds of pesticides, the probably range of recovery was from 70% to 120% in hot pepper, not detailed.…”
Section: Introductionmentioning
confidence: 99%
“…The spices of paprika are controlled for highly-persistent nonpolar pesticide residues, monitored by gas chromatography (GC) coupled to QqQ-MS/MS or time-of-flight (TOF-MS) detectors (Fernandes et al, 2014), and the various polar pesticides are assessed by UHPLC coupled to QqQ-MS/MS (Masi a, Blasco, & Pic o, 2014;Zhu, Zhao, Nan Feng, & Han Kim, 2014) and OrbitrapeHRMS (Albert, Kramer, Scheeren, & Engelhard, 2014) …”
Section: Introductionmentioning
confidence: 99%
“…Although spices contribute little to weight on our dish, they can be important contributors to our daily antioxidants [7] intake, especially in dietary cultures where spices are used regularly [8]. Due to the origin, cultivation conditions and type of processing, spices may also be a source of some contaminants such as pesticides [9,10], heavy metals [11], illegal dyes [12,13], mycotoxins [14,15] and perfluoroalkyl substances.…”
Section: Introductionmentioning
confidence: 99%